Removal of Hydrogen Sulfide Gas using Biofiltration - a Review - Cheerawit RATTANAPAN; Weerawat OUNSANEHA (Walailak Journal of Science and Technology, 2011)
Hydrogen sulfide (H2S) is extremely toxic to living organisms and plants. H2S gas contamination may be treated by both chemical and physical methods but they have high capital costs, demand large energy inputs and result in the generation of secondary hazardous wastes. Biofiltration, a biological technique, has significant economic advantages over other air pollution control technologies. Biofiltration is a process by which contaminated gases pass through the biofilter and pollutants are transported into the biofilm where they are utilized by microbes as a carbon source, an energy source. Thiobacillus sp. is the most frequently used microbial species in H2S biofiltration and can degrade H2S for energy and produce sulfate or sulfuric acid. Moreover, media selection for biofiltration (combing both natural and synthetic media) is an important step towards the development of a successful biofiltration operation. In addition, the optimization parameters of a biofiltration operation are found. First, optimal moisture content may vary from 20 to 60 wt%. Second, most microbial growths occur near neutral pH and wide deviation from these levels will impact the efficiency of the biofiltration. Third, the optimum temperature of biofiltration is near the optimum temperature for microbial inoculation based on removal efficiency. Finally, because nutrient supply is less critical as H2S removal requires few nutrients, commercial fertilizer or secondary effluent from wastewater treatment plants can be used for humid and nutrient supply. Many biofiltrations are designed for H2S control.